TuringEQ: A New Artificial Intelligence Architecture for Nonlinear Problems - Okutan, Hüseyin Enes; Baykara, Muhammet (Soner ÖZGEN, 2024)
With the developments in the field of Artificial Intelligence, the use of Artificial Intelligence has become widespread in many areas and important achievements have been achieved with the use of this technology. Most of the achievements are based on Artificial Neural Networks, which is one of the sub-fields in Artificial Intelligence. In this study, a new Artificial Intelligence Architecture that can achieve the performance level of Artificial Neural Networks is emphasized. In this study, the effects of the characteristics of these problems on the solution were examined by examining the linear and nonlinear problems, and because of these examinations, it was aimed to develop a new Artificial Intelligence Architecture that would work successfully on a basic nonlinear problem. In the study, first, a basic problem for the new Artificial Intelligence Architecture was determined. After the determination of the basic problem, studies on Artificial Intelligence architecture were started and architectural design was made on theoretical foundations. Within the scope of architecture, it is aimed to divide the problem into layers and each layer to perform the learning process within itself properly. Layer correction was made by changing the weights in the layers, which had a negative effect on the performance, in a way that would eliminate the layer defect. With these layer corrections, as the basis of the architecture, it is aimed to perform the learning process without error by correcting its own error in a way that increases the overall architectural performance of each layer. As a result of testing the Artificial Intelligence architecture, which was designed on all these theoretical foundations, on a basic nonlinear problem, it was seen that the architecture successfully performed the learning process.

ÖYapay Zekâ alanındaki gelişmelerle birlikte birçok alanda Yapay Zekâ kullanımı yaygınlaşmış ve bu teknolojinin kullanımı ile önemli başarımlar elde edilmiştir. Elde edilen başarımların büyük bir kısmı, Yapay Zekâ içerisindeki alt alanlardan biri olan Yapay Sinir Ağlarına dayanmaktadır. Bu çalışma kapsamında, Yapay Sinir Ağlarının başarım düzeyini yakalayabilecek yeni bir Yapay Zekâ Mimarisi üzerinde durulmaktadır. Bu çalışmada, doğrusal ve doğrusal olmayan problemler özelinde incelemeler yapılarak bu problemlerin karakteristiğinin çözüm üzerindeki etkileri incelenmiş ve bu incelemeler sonucunda temel bir doğrusal olmayan problem üzerinde, başarılı bir şekilde çalışacak yeni bir Yapay Zekâ Mimarisi geliştirilmesi amaçlanmıştır. Yapılan çalışmada öncelikle yeni Yapay Zekâ Mimarisi için temel bir problem belirlenmiştir. Temel problemin belirlenmesinin ardından, Yapay Zekâ Mimarisi ile ilgili çalışmalara başlanarak teorik temeller üzerinde mimari tasarım yapılmıştır. Mimari kapsamında, problem katmanlara bölünerek, her katmanın kendi içerisinde düzgün bir şekilde öğrenme işlemini gerçekleştirmesi amaçlanmıştır. Başarıma olumsuz olarak etki eden katmanlar içerisindeki ağırlıkların, katman bozukluğunu giderecek şekilde değiştirilmesi ile katman düzeltimi yapılmıştır. Bu katman düzeltileri ile mimarinin temeli olarak her katmanın genel mimari başarımını arttıracak şekilde kendi hatasını düzeltmesi ile öğrenme işleminin hatasız bir şekilde gerçekleştirilmesi amaçlanmıştır. Bütün bu teorik temeller üzerine tasarlanan Yapay Zekâ Mimarisinin, temel bir doğrusal olmayan problem üzerinde test edilmesi sonucunda mimarinin başarılı bir şekilde öğrenme işlemini gerçekleştirdiği görülmüştür.
TuringEQ: Doğrusal Olmayan Problemler Özelinde Yeni bir Yapay Zekâ Mimarisi
Keywords: Machine Learning Algorithms; Makine Öğrenmesi Algoritmaları